Improving Students' Writing Ability by using Inquiry-Based Learning Model - kasmaini, Kasmaini; zahrida, Zahrida (ENGLISH FRANCA : Academic Journal of English Language and Education, 2022)
The purpose of this study is to use an inquiry-based learning paradigm to improve the writing skills of FKIP UNIB undergraduate English education students This is a three-cycle classroom action research study. The participants in this study were 39 third-semester students. There are 3 instruments used in collecting data, namely observation, checklist, and test. The results of the observations showed an increase in understanding of the application of inquiry-based learning models from cycles one, two, and three. While from the checklist, it was seen that there was an increase in student activity from the first cycle to the third or last cycle. from the third instrument used to see the progress of students' writing skills, it can be seen that in cycle one the average student scores are 75 and 79 at the end of cycle 2 and 83.5 in the last cycle. From the three instruments above, it can be concluded that this inquiry-based learning model can increase the writing skills of English Education Study Program third-semester students, FKIP UNIB.Â